The analysis of manufacturing cycle effectiveness (MCE) in reducing non added-value activities (Empirical study at PT. Bhirawa Steel Surabaya) - Rizka Tri Verdiyanti; Rovilla El-Maghviroh (STIE Perbanas Surabaya, 2013)
The Increases of demand from costumers and the number of competitors lead companiesto reduce the cost of non value-added activities. Manufacturing Cycle Effectiveness(MCE) is commonly used as an analytical tool for production activities as well asto see how the non value-added activities are reduced and eliminated from the manufacturingprocess. Companies can reduce and eliminate non value-added activities tomaximize the value the companies. The purpose of this study is to provide empiricalevidence about the application of MCE as a measuring instrument in improving productionefficiencies and in controlling non value added activities at industrial enterprises.Based on the analysis of the MCE, the result shows that the company is notable to reduce non-value-added activities after rejuvenation of machines because thereis a lot of grunt work. The production process is still not running smoothly because alot of improvements still need to be done. Improvements during the production processresulting in decreased production process and waste a lot of waiting time. However,with the rejuvenation of machines, the company can reduce the moving time and inspectiontime.